Graph of atomic orbitals and the molecular structure-descriptors based on it - Toropov Andrey A.; Gutman Ivan; Furtula Boris (Journal of the Serbian Chemical Society, 2005)
The graph of atomic orbitals (GAO) is a novel type of molecular graph recently proposed by one of the authors. Various molecular structure-descriptors computed for GAO are compared with their analogs computed for ordinary molecular graphs. The quality of these structure-descriptors was tested for correlation with the normal boiling points of alkanes and cycloalkanes. In all the studied cases, the results based on GAO are similar to, and usually slightly better than, those obtained by means of ordinary molecular graps.